Insights into the Sesquiterpenoid Pathway by Metabolic Profiling and De novo Transcriptome Assembly of Stem-Chicory (Cichorium intybus Cultigroup “Catalogna”) - Testone, Giulio; Mele, Giovanni; Di Giacomo, Elisabetta; Gonnella, Maria; Renna, Massimiliano; Tenore, Gian Carlo; Nicolodi, Chiara; Frugis, Giovanna; Iannelli, Maria Adelaide; Arnesi, Giuseppe; Schiappa, Alessandro; Giannino, Donato (Frontiers in Plant Science, 2016)
Stem-chicory of the 'Catalogna' group is a vegetable consumed for bitter-flavored stems. Type and levels of bitter sesquiterpene lactones (STLs) participate in conferring bitterness in vegetables. The content of lactucin- and lactucopocrin-like STLs was higher in 'Molfettese' than 'Galatina' landrace stalks, regardless of the cultivation sites, consistently with bitterness scores and gustative differences. The 'Galatina' transcriptome assembly resulted in 58,872 unigenes, 77% of which were annotated, paving the way to molecular investigation of the STL pathway. Comparative transcriptome analysis allowed the identification of 69,352 SNPs and of 1,640 differentially expressed genes that maintained the pattern independently of the site. Enrichment analyses revealed that 4 out of 29 unigenes were up-regulated in 'Molfettese' vs 'Galatina' within the sesquiterpenoid pathway. The expression of two germacrene A -synthase (GAS) and one -oxidase (GAO) genes of the costunolide branch correlated positively with the contents of lactucin-like molecules, supporting that STL biosynthesis regulation occurs at the transcriptional level. Finally, 46 genes encoding transcription factors (TFs) maintained a differential expression pattern between the two varieties regardless of the growth site; correlation analyses among TFs, GAS, GAO gene expressions and STLs contents suggest that one MYB and one bHLH may act in the pathway.